A EBSERH e os seus impactos na gestão e nos serviços de saúde do Hospital das Clínicas da Universidade Federal de Pernambuco - SILVA, Rayane Diniz da (2022)
This is a study that sought to analyze the impacts of the changes promoted by the Brazilian Company of Hospital Services (EBSERH) in the management and health services of the Hospital das Clínicas of the Federal University of Pernambuco (HC-UFPE). The Federal University Hospitals (HUFs) play a prominent role in the country, as they are responsible for most of the medium and high complexity procedures within the SUS and for training a significant number of health professionals. Despite this, from the 1990s onwards, these hospital units began to face an alarming crisis situation, characterized by insufficient staff, deficient physical facilities and underutilization of installed capacity for high complexity. EBSERH is a public company that was created to solve the crisis of these hospitals through the modernization of their management. In December 2013, HC-UFPE joined EBSERH on the grounds of experiencing organizational improvements. Eight years after that adhesion, the emphasis of this research fell on the analysis of the impacts of the changes promoted by the company in the management and health services of the referred hospital. The research is characterized as exploratory and descriptive and data collection took place through documents and semistructured interviews with hospital managers. Changes in the organizational structure, the main management procedures implemented by EBSERH, were analyzed, in addition to some figures referring to the performance of the health services at HC-UFPE, based on the company's management. The results showed that the management of EBSERH has generated positive impacts on HC-UFPE, such as gains in autonomy, hospital modernization, optimization of the information process, reactivation and expansion of various services, as well as a progressive increase in the hospital's care production. However, the improvements have been gradual, and depend on permanent monitoring of the actions undertaken. Despite the positive impacts, it was detected that not all management problems were solved by EBSERH. In addition, new problems also emerged, such as the lack of practical operation of some implemented structures and the instability of the rules. The results obtained in this study can serve to guide the process of changes that is underway in the hospital.